Differences in service utilization at an urban tribal health organization before and after Alzheimer's disease or related dementia diagnosis: A cohort study. Issue 11 (25th September 2019) - Schaefer, Krista R.; Noonan, Carolyn; Mosley, Michael; Smith, Julia; Galbreath, Donna; Fenn, David; Robinson, Renee F.; Manson, Spero M.
Abstract: Introduction: The prevalence, mortality, and healthcare impact of Alaska Native and American Indian (ANAI) people with Alzheimer's disease and related dementias (ADRD) are unknown. Methods: We conducted a cohort study of electronic health record data that compared healthcare service utilization in patients with and without an ADRD diagnosis. Zero‐inflated negative binomial regression with robust standard errors was used to estimate utilization rates. Results: Compared with patients without ADRD, utilization rates were similar before but higher after ADRD diagnosis. For those with diagnosed ADRD, utilization increased gradually over time with sharp upward change during the year of diagnosis. Discussion: This is the only study quantifying changes in healthcare service utilization before and after ADRD diagnosis among ANAI people, which is crucial for tailoring geriatric care for ANAI populations.